The Role Optimizing of Election Observers in 2019 Elections - Achwan, Achwan; Kusriyah, Sri; Suharto, Rakhmat Bowo (Law Development Journal, 2021)
This study aims to analyze the role of monitoring and optimizing the role of election observers. The specification of this research is analytical descriptive with socio-legal approach method. The method of collecting data is by interviewing and analyzing data from laws and regulations, research results, scientific works and relevant books. The results of this study indicate that election monitoring plays an important role in the quality of elections, namely complementing the limitations of Bawaslu in terms of the number of supervisory personnel and the breadth of the scope of its supervision, as a form of public participation, as an election control institution, as part of citizen political education and as a balance between election organizers. . To optimize the role of election observers, this can be done by: registration for accreditation is carried out at the beginning of the stages, election monitoring is carried out at all stages, the need for mastery and understanding of all election regulations, the need for sources of funds other than member fees such as budget assistance from the government or in collaboration with donor agencies that not affiliated with any election contestants or political parties,Â